Dynamic change of circulating innate and adaptive lymphocytes subtypes during a cascade of gastric lesions. Issue 4 (3rd June 2022) - Fu, Weiwei; Wang, Wenyan; zhang, Jing; Zhao, Yang; Chen, Keyan; Wang, Ye; Zhang, Jing; Xiong, Ying; Guo, Xiaohuan; Ding, Shigang
Abstract: According to the Correa model, the intestinal-type gastric cancer (GC) is preceded by premalignant lesions, including chronic gastritis, intestinal metaplasia and dysplasia. However, the dynamic change of innate and adaptive immune response during this process has not been studied comprehensively. In this study, we performed a comprehensive and trajectory analysis of circulating innate lymphoid cells (ILCs) and adaptive Th lymphocytes subtypes in patients spanning a cascade of gastric lesions. Increased circulating ILC2s frequency was found in the gastritis, premalignant stage and GC group, whereas further decreased ILC2s were detected in the GC group compared with the premalignant group. Moreover, ILC3s level was higher in both gastritis, premalignant lesion and GC stage, compared with healthy controls. Furthermore, up-regulated T follicular helper (Tfh) cell proportions were detected in the gastritis and premalignant process. In conclusion, by analyzing the circulating ILCs and Th cells frequency and the key cytokine production or immunoglobulin level, we demonstrated the potential involvement of ILC3 and Tfh in the gastric diseases. These findings will help to understand the immunologic mechanisms in both GC and the premalignant process and contribute to serve potential therapeutic targets to prevent the GC development. Graphical Abstract: A trajectory analysis of circulating ILCs and adaptive T cell lymphocytes subtypes in patients spanning a cascade of gastric lesions.